Implementasi Sistem Keamanan Data Menggunakan Algoritma Kriptografi Asimetris Elliptic Curve Cryptography (ECC) Berbasis Website - Iqlima, Putri; Rayyan, Muhammad; Rambe, Az Zahra Alfansuri; Ardina, Elin; Lubis, Delia Fitri Anggriani; Ismawati, Dea (JIKUM: Jurnal Ilmu Komputer, 2025)
Data security is very important in the digital world, especially to protect personal data, financial transactions, and sensitive communications. One method used to maintain information security is cryptography, specifically Elliptic Curve Cryptography (ECC). ECC offers a level of security equivalent to other algorithms such as RSA, but with a smaller key size, making it more efficient in resource usage. This web-based system allows users to encrypt and decrypt messages using public and private keys. Although effective in maintaining data security, this system still requires manual input of keys by the user, which is prone to errors. Further development is needed to improve key management and user convenience.